Novel relatives of Mecsek Mountains mammarenavirus (family Arenaviridae) in hedgehogs living in different sampling areas in Hungary - Károly Takáts; Péter Pankovics; Benigna Balázs; Ákos Boros; Róbert Mátics; Gábor Reuter (Scientific Reports)
Abstract Mammarenaviruses (genus Mammarenavirus, family Arenaviridae) are rodent-borne zoonotic viruses consisting of 52 viral species, including ten that are pathogenic to humans. Currently, only two endemic mammarenavirus species are known in Europe: the human pathogenic Mammarenavirus choriomeningitidis (LCMV) and the recently discovered hedgehog-origin Mammarenavirus mecsekense (MEMV). In this study, 59 faecal specimens from Northern white-breasted hedgehogs (Erinaceus roumanicus) from different geographic regions in Hungary were investigated for mammarenavirus presence and complete genome characterization using newly designed screening primers by RT-semi-nested PCR and sequencing methods. Five (8.5%) of the 59 samples tested positive for mammarenavirus RNA (ER8, ER15, ER27, ER33, and ER39, GenBank accession numbers PQ441959-PQ441968). The L- and S-segments of these strains showed 66–93% and 73–92% nt identity to the closest known mammarenavirus, MEMV, respectively. The NP protein exhibited 86–97% aa sequence identity compared to the corresponding protein of MEMV. Notably, the S-segment intergenic region (S-IGR) of strains ER8, ER15, ER27 and ER33 exceeded the average nt length among known mammarenaviruses and contained two, highly similar stem-loop structures with conserved self-complementary nucleotide motifs. Based on the sequence- and phylogenetic analysis these strains (ER8, ER15, ER27 and ER33) potentially represent a novel mammarenavirus species, tentatively named Pannonia mammarenavirus (PANV).